Extraction of iron from coal bottom ash by carbon reduction method - Itam Z.; Kamal N.L.M.; Syamsir A.; Beddu S.; Muhammad D.; Zahari N.M.; Kai L.M.; Hamid Z.A.A.; Razak N.A. (American Institute of Physics Inc., 2023)
Most of the world's energy production is still mainly achieved by the combustion of coal in power stations. In Malaysia, seven power plants under Tenaga Nasional Berhad Malaysia (TNB) continuously produce around 790 tons of Coal Bottom Ash (CBA) per day. These vast volumes pose a problem in the disposal of the CBA which conventionally is loaded onto ash landfills. Many of the metals and oxides contained by the CBA are environmentally hazardous. When the CBA is disposed in landfills, the metal oxides are leached out and find their way into potable water and into animal and plantations. Disposal of the unused CBA is costly and poses financial disadvantages to power station and to the environment. However, the metals contained inside the CBA may be valuable to various industry if there is a way to extract the metals out of the CBA. This study focused on investigating the extraction of iron from coal bottom ash by the carbon reduction method. The rationale for this process was that by removing and recovering these major constituent elements from the ash, it would be easier to concentrate and isolate the trace elements especially the rare earth elements that are present in the CBA. The chemical composition of the CBA is then determined by x-ray fluorescence. The main mineral phases in CBA were determined to be quartz, aluminium oxide and iron (III) oxide. The experimental results obtained from the carbon reduction method showed that the optimum time for the reduction of iron (III) oxide by carbon from CBA is 30 minutes and the optimum temperature for the reduction is 800C. 2018 Author(s).